Synergistic effect between oxides semiconductors and zeolites on photobleaching of RB250 textile dye - Vicentini, Jean César Marinozi; Medeiros, Gabriela Brunosi; Watanabe, Maria Clara Chimirri; Piccoli, Karen Raiane; Camilo, Fernanda Carla; Scaliante, Mara Heloisa Neves Olsen (Acta Scientiarum. Technology, 2018)
The present work aims to evaluate the activity of semiconductor oxides (TiO2, Nb2O5 and ZnO) supported on NaA and NaY zeolites, as well as their synergistic effect on Reactive Blue Dye (RB250) photodegradation process. Prior to deposition, TiO2 particles size was reduced by ultrasonic scattering followed by filtration. The particles on the filtrate were used to conduct the experiments. The semiconductors were immobilized in concentrations of 2.5, 5 and 10% (w w-1) and the photocatalytic tests were performed at catalyst concentrations of 1 and 2 g L-1. Moreover, supported catalysts were characterized by XRD, textural analysis, zero point of charge and temperature programmed desorption of NH3. A comparison between the supported catalysts showed high activity for the ones supported with ZnO and TiO2. Zeolite NaY has broader opened channels than NaA, which reduces the dye molecules blockage, and, as a result, increased the catalyst activity. A higher concentration of supported catalysts (2 g L-1) provides greater photocatalytic activity, while higher concentration of semiconductors immobilized on supports does not present significant differences. Â 